APPLICATION OF AEROSPACE METHODS FOR DETERMINING THE EFFICIENCY OF LAND USE TRANSCARPATHIA - Железняк, О. О.; Гебрин, Л. В. (Science-based technologies, 2014)
The state of land resources and productivity of agricultural land Transcarpathian region and Mukachevo district in particular. Conducted to determine the effectiveness of land use in the region. The main problem of optimized land use and land management. Made basic properties of soil fertility for example Rakoshynskoyi village council. The dynamic change of vegetation from multispectral satellite image Landsat 8 using a combination of RGB ( natural colors ) and vegetation index NDVI is calculated using the channel RED and NIR. The measures to address the deficiencies of modern land use in the region through the use of aerospace methods of removal and GIS technology to improve the efficiency of land use.